2018
DOI: 10.1093/cid/ciy1077
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role for Metronidazole in the Treatment of Clostridium difficile Infection? Results From a National Cohort Study of Veterans With Initial Mild Disease

Abstract: Background Metronidazole may still be an appropriate therapeutic option for mild Clostridium difficile infection (CDI) in select patients, but data are limited to guide clinicians in identifying these patients. Methods Our 2-stage study included a national cohort of Veterans with a first episode of mild CDI (2010–2014). First, among those treated with metronidazole, we identified predictors of success, defined as absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…CDI is not restricted to this type, however, as infections caused by RT001, RT002, RT014/020, and RT078 are frequently reported in both Europe and the United States 7,8 . Metronidazole is used for the treatment of mild-to-moderate infections and vancomycin for severe infections, though vancomycin is increasingly indicated as a general first-line treatment [9][10][11][12][13][14][15][16] . Fidaxomicin has recently also been approved for CDI treatment, but its use is limited by high costs 12 .…”
mentioning
confidence: 99%
“…CDI is not restricted to this type, however, as infections caused by RT001, RT002, RT014/020, and RT078 are frequently reported in both Europe and the United States 7,8 . Metronidazole is used for the treatment of mild-to-moderate infections and vancomycin for severe infections, though vancomycin is increasingly indicated as a general first-line treatment [9][10][11][12][13][14][15][16] . Fidaxomicin has recently also been approved for CDI treatment, but its use is limited by high costs 12 .…”
mentioning
confidence: 99%
“…3,12,14 One recent study examined patients under 65 and found no significant differences between the use of vancomycin and metronidazole in milder cases. 13 After factoring in patient mortality, our study demonstrated no differences mortality among surviving patients between outpatients and inpatients. 3,6,11 This again raises the question of metronidazole prescriptions in the clinic setting, as these findings are not consistent with the 2017 CDI guidelines.…”
Section: Discussionmentioning
confidence: 60%
“…For those clinic-based providers who opt to use metronidazole, this raises issues due to possibility of missing potential cases of severe CDI and treatment appropriateness. 3,4,6,[11][12][13] In this sample, physicians in the control group (hospital patient) were more likely to adhere to the 2010 CDI guidelines. (Table 2) However, this difference was likely accounted for mostly by a significant number of clinic-based physicians prescribing oral vancomycin instead of metronida-zole, which is now consistent with first-line therapy according to the 2017 IDSA Guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…Some guidelines recommend the use of metronidazole for the treatment of CDI ( Abreu et al., 2019 ; Sartelli et al., 2019 ; Xu et al., 2020 ; Baunwall et al., 2021 ; Johnson et al., 2021 ; Kelly et al., 2021 ). Efficacy analysis of one study ( Appaneal et al., 2019 ) show that metronidazole is not different from vancomycin in the risk of all-cause mortality or recurrence of CDI within 30 days, and the cost of metronidazole is lower than that of vancomycin; guidelines do not recommend the use of metronidazole for the treatment of CDI ( Antonelli et al., 2020 ; Lewis et al., 2021 ; Poylin et al., 2021 ). A Cochrane review ( Nelson et al., 2017 ) show that in terms of its cure rate, vancomycin (79%) is more effective than metronidazole (72%; relative risk (RR) 0.90; 95% CI (0.84–0.97)), and metronidazole had potential side effects and a higher recurrence rate.…”
Section: Discussionmentioning
confidence: 99%